Self-Esteem, Body Image, and The Tendency Of Body Dysmorphic Disorder (BDD) in Generation Z - Norfilita Toba Lamba (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
The impact of social media on Generation Z has resulted in the development of self-perception standards based on influencers' appearance. Body dysmorphic disorder (BDD) is characterized by individuals' negative thoughts about their physical appearance. Individuals with positive self-esteem and body image are less likely to experience body-related disorders. This study aims to examine the impact of body image and self-esteem on the tendency of BDD among young adults. The study utilized a quantitative approach, employing a multiple linear regression analysis on data collected from young adults. The findings of the study revealed a significant negative relationship between self-esteem and BDD, indicating that higher self-esteem is associated with lower BDD tendencies. Furthermore, body image was also found to have a significant impact on BDD. The study concludes that both self-esteem and body image play crucial roles in influencing the likelihood of BDD development, with self-esteem having a greater impact. These findings highlight the importance of promoting positive body image and self-esteem in order to mitigate the prevalence of BDD among young adults.